SECURITY AND PRIVACY IN CRYPTOVALUTA TRANSACTIONS: AN ANALYSIS OF THE LITERATURE ON BLOCKCHAIN TECHNOLOGY - Gunawan Widjaja (CV. Adiba Aisha Amira, 2024)
Blockchain technology has revolutionised many industry sectors, including finance, through the introduction of cryptovaluta. While it offers significant transparency and decentralisation, it also raises serious challenges related to security and privacy. This article analyses the existing literature to evaluate various aspects of security and privacy in cryptovaluta transactions. The transparency of blockchain, while increasing trust, may result in the risk of disclosure of user identity and transaction details. Advanced technologies such as zk-SNARKs and CoinJoin have been developed to address this issue, enabling the scrutiny of transactions without revealing sensitive information. The security of blockchain networks, while inherently robust, remains vulnerable to attacks aimed at individual users and exchange platforms. Digital wallet theft, phishing attacks, and vulnerabilities in smart contracts are some of the significant risks. The article also emphasises the importance of user education to recognise and address these risks. By combining more advanced security technologies with increased user awareness, it is hoped that an optimal balance between transparency, privacy, and security can be achieved in the cryptocurrency ecosystem.